IMPROVISATION AS A MEANS OF SHAPING THE PROFESSIONALISM OF FUTURE TEACHERS - Otajonov Jamshid Mashrabjonovich; Ro'zimatova Dilnozaxon To'lqinboy qizi (Journals Park Publishing, 2022)
The article examines the development of future teachers' improvisation as an integral part of pedagogical skills. Theoretical ideas are supported by examples.
Keywords: improvisation, potential opportunity